Water quality. Determination of total organic carbon (TOC), dissolved organic carbon (DOC), total bound nitrogen (TNb ) and dissolved bound nitrogen (DNb ) after high temperature catalytic oxidative combustion. (31st March 2022) - British Standards Institution,
No abstract available